Association between timely targeted treatment and outcomes in patients with metastatic HER2‐overexpressing gastroesophageal adenocarcinoma. Issue 9 (4th February 2022) - Lau‐Min, Kelsey S.; Li, Yimei; Eads, Jennifer R.; Mamtani, Ronac; Getz, Kelly D.
Abstract : Background: Timely targeted treatment initiation can be challenging because additional biomarker testing is needed for eligibility. The authors hypothesized that timely targeted treatment improves survival relative to nontimely initiation in metastatic HER2+ gastroesophageal adenocarcinoma (GEA). Methods: The authors performed a retrospective cohort study of metastatic HER2+ GEA treated with first‐line (1L) systemic therapy from January 2011 to December 2017 using a nationwide electronic health record–derived deidentified database. Timely targeted treatment—trastuzumab initiation within 14 days after starting 1L chemotherapy—was assessed as a time‐varying exposure. Nontimely targeted treatment included patients who initiated trastuzumab after 14 days or who lacked documentation of receiving trastuzumab. Extended Cox regressions compared overall survival (OS) and progression‐free survival (PFS) between timely and nontimely groups. Results: A total of 320 patients were included; 59.1% received timely trastuzumab. Relative to nontimely initiation, timely trastuzumab was associated with significantly higher OS (2‐year OS, 32.1% vs 15.3%; adjusted hazard ratio [HR], 0.67; 95% CI, 0.51‐0.88) and PFS (2‐year PFS, 9.2% vs 3.7%; adjusted HR, 0.71; 95% CI, 0.55‐0.93). Results remained similar in sensitivity analyses 1) using alternative "timeliness" definitions up to 70 days after starting 1L chemotherapy, 2) comparing any trastuzumab, regardless of timing of initiation, to no trastuzumab, and 3) excluding patients lacking documentation of receiving trastuzumab. Conclusions: Improved survival was observed among metastatic HER2+ GEA patients treated with trastuzumab versus those who were not, regardless of timing of initiation. Although these results reassure clinicians that modest targeted treatment delays may not be detrimental to outcomes, efforts should still ensure that all metastatic HER2+ GEA patients receive trastuzumab. Abstract : Time‐to‐treatment initiation is an important quality metric in oncology, but there is a paucity of data on the impact of timely targeted treatment for which additional biomarker testing is needed to identify eligible patients. In this study of patients with metastatic HER2‐overexpressing gastroesophageal adenocarcinoma, overall and progression‐free survival rates were higher for patients treated with trastuzumab compared to those who were not, regardless of the timing of initiation.